Cholesterol-tethered platinum II-based supramolecular nanoparticle increases antitumor efficacy and reduces nephrotoxicity - Sengupta, Poulomi; Basu, Sudipta; Soni, Shivani; Pandey, Ambarish; Roy, Bhaskar; Oh, Michael S.; Chin, Kenneth T.; Paraskar, Abhimanyu S.; Sarangi, Sasmit; Connor, Yamicia; Sabbisetti, Venkata S.; Kopparam, Jawahar; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Nanoscale drug delivery vehicles have been harnessed extensively as carriers for cancer chemotherapeutics. However, traditional pharmaceutical approaches for nanoformulation have been a challenge with molecules that exhibit incompatible physicochemical properties, such as platinum-based chemotherapeutics. Here we propose a paradigm based on rational design of active molecules that facilitate supramolecular assembly in the nanoscale dimension. Using cisplatin as a template, we describe the synthesis of a unique platinum (II) tethered to a cholesterol backbone via a unique monocarboxylato and O -> Pt coordination environment that facilitates nanoparticle assembly with a fixed ratio of phosphatidylcholine and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine- N-[amino (polyethylene glycol)-2000]. The nanoparticles formed exhibit lower IC50 values compared with carboplatin or cisplatin in vitro, and are active in cisplatin-resistant conditions. Additionally, the nanoparticles exhibit significantly enhanced in vivo antitumor efficacy in murine 4T1 breast cancer and in K-Ras(LSL/+/)Pten(fl/fl) ovarian cancer models with decreased systemic- and nephro-toxicity. Our results indicate that integrating rational drug design and supramolecular nanochemistry can emerge as a powerful strategy for drug development. Furthermore, given that platinum-based chemotherapeutics form the frontline therapy for a broad range of cancers, the increased efficacy and toxicity profile indicate the constructed nanostructure could translate into a nextgeneration platinum-based agent in the clinics.
Keywords: chemotherapy; nanomedicine